Mental Toughness Development via Military-Style Training in the NCAA: A Three-Phase, Mixed-Method Study of the Perspectives of Strength and Conditioning Coaches - Andreas Stamatis; Grant B. Morgan; Patrick Nyamaruze; Panagiotis Koutakis (Sports, 2022)
Sport cultures transmit values for anticipated conduct. Recent events have resulted in injuries/deaths of National Collegiate Athletic Association (NCAA) student-athletes, usually during off-season football training. Through media reports, strength and conditioning coaches (SCC) have been allegedly involved by incorporating military-style training (MST). Mental toughness (MT) has been associated with hypermasculine subcultures in sports. For the first time, perceptions of collegiate SCCs were chosen to contribute to the development of cultural best practices in sports, via a multiphase mixed-method design (Phase 1, n = 465; Phase 2, n = 72; Phase 3, n = 99). Quantitative and qualitative data were collected aiming to confirm and explore the use of MST in the NCAA, its connection to SCCs, its association with MT development, and the role of the media. MST is uncommon in the NCAA. MST takes place mostly during the off-season in the form of physical, in-scope protocols while football is the most common sport. MST promotes MT. The recent media backlash is considered unfounded. Cultures promoted by SCCs do not indicate conformity of student-athletes to unethical/unhealthy expectations. Future sport psychology research and practice should continue to prioritize culture, cultural identities, and physical and mental well-being.